2013
DOI: 10.1212/wnl.0b013e3182a4a4d2
|View full text |Cite
|
Sign up to set email alerts
|

Helsinki model cut stroke thrombolysis delays to 25 minutes in Melbourne in only 4 months

Abstract: We demonstrated rapid transferability of an optimized tPA protocol to a different health care setting. With the cooperation of ambulance, emergency, and stroke teams, we succeeded in the absence of a dedicated neurologic emergency department or electronic patient records, which are features of the Finnish system. The next challenge is providing the same service out-of-hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
216
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(237 citation statements)
references
References 16 publications
11
216
0
10
Order By: Relevance
“…A study in Melbourne recently showed the rapid transferability of the Helsinki thrombolysis model, achieving a 25-minute interval within 8 months of changing protocol. 25 Improving in-hospital processes is feasible because they are controlled by a relatively small number of people. Canada has made progress in this regard in the last decade.…”
Section: Cmaj Openmentioning
confidence: 99%
“…A study in Melbourne recently showed the rapid transferability of the Helsinki thrombolysis model, achieving a 25-minute interval within 8 months of changing protocol. 25 Improving in-hospital processes is feasible because they are controlled by a relatively small number of people. Canada has made progress in this regard in the last decade.…”
Section: Cmaj Openmentioning
confidence: 99%
“…Previous studies have shown that the treatment performed by neurology experts and the implementation of simple measures reduced the DNT 4,5,10,15 . In the current study, not only we were able to implement similar measures throughout the study's period, but we also provided patients admitted in the TB group with an additional simple measure, an exclusive bed for IVT treatment.…”
Section: Gabriella Tansini Et Al Bed For Thrombolysis Reduces Door-tmentioning
confidence: 99%
“…These analyses were similar to a previously reported study 3 . Throughout the study's period, neurologists were responsible for coordinating the teams and similar measures compared to those done by previous studies were done during all the study period 4,5,10 . During the study period, a total of 150 ischemic stroke patients were admitted following EMS evaluation and were submitted to IVT; 71 (47.3%) were admitted in the first period of the study and composed the ER Group, whereas the other 79 (52.7%) were admitted in the second part of the study and composed the TB Group.…”
Section: In-hospital Patient's Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…18 This model was replicated at the Royal Melbourne Hospital, where median door-to-needle times were reduced from 61 minutes to 25 minutes. 19 Improvements in the United States (US) have been reported by the Target-Stroke initiative. 20,21 Importantly, these improvements in door-to-needle treatment time have not resulted in an increase in complications.…”
mentioning
confidence: 99%